Design of New Nonisolated High Gain Converter for Higher Power Density - Ramachandran Rajesh; Natarajan Prabaharan (International Transactions on Electrical Energy Systems, 2023)
A high gain nonisolated DC-DC converter using a single power semiconductor switch is proposed in this article. The operation of the proposed converter is explained under continuous conduction mode (CCM), discontinuous conduction mode (DCM), and boundary conduction mode (BCM). The mathematical expressions for steady-state voltage gain, voltage stress, and current stress of diodes and switch are provided. Also, the design of inductors and capacitors in the CCM mode is explained with appropriate mathematical equations. The proposed topology is tested with a 200 W prototype at 50 kHz and a 60% duty cycle. The dynamic behavior of the proposed converter is examined by changing the duty cycle value and also load values. The proposed converter is verified with experimental results to prove the effectiveness of its operation. The proposed converter provides higher steady-state voltage gain as compared with recently developed topologies. The efficiency and power density of the proposed converter is 90% and 1.16 kW/L, respectively.